Pengembangan Media Pembelajaran Audio-Visual pada Mata Pelajaran Ilmu Pengetahuan Alam Sosial Kelas IV MI Bahrul Ulum Kemlagilor - Kamiliyah, Arifatul (AJER: Advanced Journal of Education and Religion, 2025)
The main problem of this research is that the learning process in various subjects is still dominated by teachers using conventional learning models and only using printed teaching materials, while existing facilities in schools, such as digital television, have not been maximized for the teaching and learning process. The purpose of this study is to determine the development and effectiveness of Audio-Visual Learning Media for Social Sciences in Grade IV of MI Bahrul Ulum Kemlagilor. The Research and Development method used in this study is the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The validators in this study were 3 people (material experts, media experts and educators) and 3 class teachers. The limited trial subjects in this study were 10 fourth grade students. The data collection technique used was an assessment instrument sheet. The results of the pre-test and post-test were calculated using the Wilcoxon test. The results of the expert assessment obtained a score of 95.00% from material experts, 96.00% from media experts, and 86.09% from educators. while from the teacher trial obtained 89.36%, 80.85%, and also 74.46%.. based on the effectiveness results Here there are "10" positive data (N) which means that the 10 students experienced an increase from the Pre-Test score to the Post-Test score. The Mean Ranks or average increase is "5.50", while the number of positive rankings or Sum of Ranks is "55.00". so it can be concluded that the use of audio-visual media is effective in stimulating understanding of science material and improving the learning of fourth grade students at Mi Bahrul Ulum Kemlagilor.